Carryover Effects of Crude Glycerin Fed During the Growing Phase on Finishing Cattle Performance and Carcass Characteristics - C. C. Aperce; J. S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2012)
Crude glycerin is a byproduct of biodiesel production, and its use as a feedstuff for cattle has expanded in the last decade due to increased availability and favorable pricing compared with other energy concentrates such as cereal grains. Incorporation of glycerin into cereal-based finishing diets, at levels up to 8%, has been shown to improve cattle performance; however, it decreases activity of cellulolytic microorganisms in the rumen, ultimately decreasing fiber digestion. Most of the studies conducted to date have evaluated glycerin in finishing diets that contain relatively small amounts of fiber, but little is known of its value as an energy source for growing cattle that typically are fed diets containing greater proportions of fiber. Moreover, possible carryover effects from feeding glycerin in the growing phase and effects on finishing performance and carcass characteristics are unknown. In this study, we wanted to evaluate glycerin as a component of diets fed throughout a 90-day backgrounding phase to determine its impact on performance and carcass characteristics of heifers during the subsequent finishing phase when they were no longer fed glycerin.
Keywords: beef cattle